Estimating the Geographic Distribution of Host-Seeking Adult Amblyomma americanum (Acari: Ixodidae) in Florida. Issue 1 (30th August 2018) - Kessler, William H; Blackburn, Jason K; Sayler, Katherine A; Glass, Gregory E
Abstract: The lone star tick, Amblyomma americanum, is the most commonly reported human-biting tick in the southeastern United States and is a vector for several human and livestock pathogens. Although it is endemic to Florida, little is known about the ecological preferences and current spatial distribution within the state. Using occurrence records of adult A. americanum collected between August 2015 and September 2016, a logistic regression model was used to estimate environmental associations, as well as to predict the distribution of the tick at a one hectare resolution. Occurrence of adult lone star ticks was associated with land cover and bioclimatic variables, namely the presence of forested areas and precipitation seasonality. The estimated spatial distribution indicated that central and northern regions show greater suitability than the southern half of the state. Furthermore, areas predicted to be suitable for the species decreases from north to south with very little area deemed suitable in the far southern reaches of the state. High heterogeneity in the distribution of suitable habitat has implications for the distribution of tick-borne disease cases in the state. The subcounty resolution of the estimated distribution is an improvement over distributions currently published and may better inform the public and state or federal agencies of potential risk of exposure to A. americanum and its associated pathogens.